Training workshop on research to inform agricultural and food security policy and practice in Kenya, 19–21 February 2018 - Karugia, Joseph T. (2018)
The International Livestock Research Institute (ILRI) and the Swedish AgriFoSe2030 program, organized a three-day training workshop titled “Research to inform agricultural and food security policy and practice in Kenya” at ILRI Campus, Nairobi on 19th – 21st February 2018. The workshop targeted Kenyan researchers who recently attained PhD qualifications and are working on agriculture and food security issues. A total of eleven (11) participants (7 men and 4 women) from different Universities and research organizations in Kenya namely: University of Nairobi, University of Eldoret, Embu University, Chuka University and Kenya Agricultural and Livestock Research Organization (KARLO) participated in the workshop.